Why Are Artists Poor? The Exceptional Economy of the Arts - Abbing, Hans (Amsterdam University Press, 2008)
Most artists earn very little. Nevertheless, there is no shortage of aspiring young artists. Do they give to the arts willingly or unknowingly? Governments and other institutions also give to the arts, to raise the low incomes. But their support is ineffective: subsidies only increase the artists' poverty. The economy of the arts is exceptional. Although the arts operate successfully in the marketplace, their natural affinity is with gift-giving, rather than with commercial exchange. People believe that artists are selflessly dedicated to art, that price does not reflect quality, and that the arts are free. But is it true? This unconventional multidisciplinary analysis explains the exceptional economy of the arts. Insightful illustrations from the practice of a visual artist support the analysis.